Complex amplitude reconstruction by iterative amplitude-phase retrieval algorithm with reference. (June 2018) - Shen, Cheng; Guo, Cheng; Tan, Jiubin; Liu, Shutian; Liu, Zhengjun
Highlights: A new multi-image phase retrieval algorithm is proposed. The mismatch of distance measurements in multi-image phase retrieval is solved. More accurate reconstruction result and faster convergence speed is achieved in simulation and experiments. A prototype of a compact holographic image sensor is proposed. Abstract: Multi-image iterative phase retrieval methods have been successfully applied in plenty of research fields due to their simple but efficient implementation. However, there is a mismatch between the measurement of the first long imaging distance and the sequential interval. In this paper, an amplitude-phase retrieval algorithm with reference is put forward without additional measurements or priori knowledge. It gets rid of measuring the first imaging distance. With a designed update formula, it significantly raises the convergence speed and the reconstruction fidelity, especially in phase retrieval. Its superiority over the original amplitude-phase retrieval (APR) method is validated by numerical analysis and experiments. Furthermore, it provides a conceptual design of a compact holographic image sensor, which can achieve numerical refocusing easily.